2011
DOI: 10.1097/lbr.0b013e318235d805
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis of Bronchus in Lung Cancer

Abstract: Bronchial necrosis with wall destruction and direct visualization into the cavity is seldom described in the context of lung cancer, except after radiation therapy. We describe 5 cases of cavitating lung cancer with direct communication with the airways, large enough to allow the passage of a flexible bronchoscope. We encountered all of these cases between May 2009 and January 2010. None of the patients had received radiation previously. During bronchoscopy, necrosis of the bronchus was evident with replacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…We found that BgRT and IMPT would produce similar maximum doses to 1 cc of the aorta and thus equivalent 1 cc composite doses. Additionally, a lower bronchus V 40 (11% lower in the BgRT plan than VMAT and 8% lower than in the IMPT plan) could reduce the risk of radiation-induced bronchial necrosis (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…We found that BgRT and IMPT would produce similar maximum doses to 1 cc of the aorta and thus equivalent 1 cc composite doses. Additionally, a lower bronchus V 40 (11% lower in the BgRT plan than VMAT and 8% lower than in the IMPT plan) could reduce the risk of radiation-induced bronchial necrosis (20,21).…”
Section: Discussionmentioning
confidence: 99%